hERG K+ Channels Promote Survival of Irradiated Leukemia Cells - Palme, Daniela; Misovic, Milan; Ganser, Katrin; Klumpp, Lukas; Salih, Helmut R.; Zips, Daniel; Huber, Stephan M. (Frontiers in Pharmacology, 2020)
Many tumor cells express highly elevated activities of voltage-gated K+ channels in the plasma membrane which are indispensable for tumor growth. To test for K+ channel function during DNA damage response, we subjected human chronic myeloid leukemia (CML) cells to sub-lethal doses of ionizing radiation (0–8 Gy, 6 MV photons) and determined K+ channel activity, K+ channel-dependent Ca2+ signaling, cell cycle progression, DNA repair, and clonogenic survival by whole-cell patch clamp recording, fura-2 Ca2+ imaging, Western blotting, flow cytometry, immunofluorescence microscopy, and pre-plating colony formation assay, respectively. As a result, the human erythroid CML cell line K562 and primary human CML cells functionally expressed hERG1. Irradiation stimulated in both cell types an increase in the activity of hERG1 K+ channels which became apparent 1–2 h post-irradiation. This increase in K+ channel activity was paralleled by an accumulation in S phase of cell cycle followed by a G2/M cell cycle arrest as analyzed between 8 and 72 h post-irradiation. Attenuating the K+ channel function by applying the hERG1 channel inhibitor E4031 modulated Ca2+ signaling, impaired inhibition of the mitosis promoting subunit cdc2, overrode cell cycle arrest, and decreased clonogenic survival of the irradiated cells but did not affect repair of DNA double strand breaks suggesting a critical role of the hERG1 K+ channels for the Ca2+ signaling and the cell cycle control during DNA damage response.